Fertility studies on some Vicia faba L. populations - Lim, Eng Siong; Knight, R. (1979)
Vida faba is an important grain legume in many countries of the world but is rarely grown in Australia. It is being considered as a grain crop to replace the normal leguminous pasture used in the cereal-pasture rotation practised in southern Australia. Most of the research and agronomic information on the crop has been derived from work in Europe. There the crop has a reputation for wide fluctuations in yield (Rowlands, 1955, Scriven, Cooper and Allen, 1961). Although the weather and agronomic practices can cause fluctuations, variable pollination was also considered responsible (Drayner, 1959).